Recognition of two classes of oligoproline sequences in profilin- mediated acceleration of actin-based Shigella motility (The Rockefeller University Press, 1996)
The gram negative rod Shigella flexneri uses it surface protein IcsA to induce host cell actin assembly and to achieve intracellular motility. Yet, the IcsA protein lacks the oligoproline sequences found in ActA, the surface protein required for locomotion of the gram positive rod Listeria monocytogenes. Microinjection of a peptide matching the second ActA oligoproline repeat (FEFPPPPTDE) stops Listeria locomotion (Southwick, F.S., and D.L. Purich. 1994a. Proc. Natl. Acad. Sci. USA. 91:5168-5172), and submicromolar concentrations (intracellular concentration 80-800 nM) similarly arrest Shigella rocket-tail assembly and intracellular motility. Coinjection of a binary solution containing profilin and the ActA analogue increased the observed rates of intracellular motility by a factor of three (mean velocity 0.90 +/- 0.07 mu m/s, SD n=16 before injection vs 0.3 +/- 0.1 mu m/s, n=33 postinjection, intracellular concentration = 80 nM profilin plus 80 nM ActA analogue). Recent evidence suggests the ActA analogue may act by displacing the profilin-binding protein VASP (Pistor, S.C., T. Chakaborty, V. Walter, and J. Wehland. 1995. Curr. Biol. 5:517-525). At considerably higher intracellular concentrations (10 muM), the VASP oligoproline sequence (GPPPPP)3 thought to represent the profilin- binding site (Reinhard, M., K. Giehl, K. Abel, C. Haffner, T. Jarchau, V. Hoppe, B.M. Jockusch, and U. Walter. 1995. EMBO (Eur. Mol. Biol. Organ.) J. 14:1583-1589) also inhibited Shigella movement. A binary mixture of the VASP analogue and profilin (each 10 muM intracellular concentration) led to a doubling of Shigella intracellular migration velocity (0.09 +/- 0.06 mu m/s, n = 25 preinjection vs 0.18 +/- 0.10 mu m/s, n = 61 postinjection). Thus, the two structurally divergent bacteria, Listeria and Shigella, have adopted convergent mechanisms involving profilin recognition of VASP oligoproline sequences and VASP recognition of oligoproline sequences in ActA or an ActA-like host protein to induce host cell actin assembly and to provide the force for intracellular locomotion and cell-cell spread.